Prototype of Secure Exam Browser during Online Examnination - Hadi Salleh, (Journal of Computing Technologies and Creative Content, 2025)
The secure exam browser is an innovative tool that enhances the reliability and security of online exams by integrating face recognition and tracking technology. It captures the student's face before the exam to ensure accurate identification and reduce the risk of impersonation. During the exam, the system continuously monitors the student's face to maintain exam integrity and detect any suspicious behavior. This tool provides several benefits, including real-time surveillance that reduces the likelihood of cheating. It streamlines the authentication process, eliminating the need for extensive manual invigilation and improving the overall test experience. The secure exam browser has undergone rigorous testing, proving its effectiveness in capturing and verifying face characteristics while monitoring for anomalies. With its user-friendly design, compatibility with various devices and browsers, and robust security features, it safeguards the validity of exams and prevents unauthorized access. For educational organizations and institutions concerned about protecting the integrity of online examinations, the secure exam browser is an invaluable asset. It ensures secure authentication and monitoring through sophisticated facial recognition and tracking capabilities, creating a dependable and trustworthy environment for conducting high-stakes exams.